METHODOLOGY FOR DEVELOPING TRANSVERSAL COMPETENCIES OF FUTURE TEACHERS BASED ON PROFESSIONAL REFLECTION - Askarova Barchinoy Abdirakhimovna (Web of Journals Publishing, 2025)
This article is dedicated to the methodology of developing transversal competencies of future teachers through professional reflection. Transversal competencies play a crucial role in ensuring a teacher's successful performance in the modern education system, while professional reflection serves as an effective tool for fostering these competencies. The article examines the methodology for developing transversal competencies based on professional reflection and identifies the most effective teaching methods.
Keywords: Modern education, mastery, professional reflection, transversal competence, skills, knowledge, qualifications, methods, digital literacy, innovative activity.